Case Report: Ileo-Ileal Intussusception Secondary to Inflammatory Fibroid Polyp: A Rare Cause of Intestinal Obstruction - Guerci, Claudio; Colombo, Francesco; Goi, Gloria; Zerbi, Pietro; Pirrò, Barbara; Danelli, Piergiorgio (Frontiers in Surgery, 2022)
Introduction Intussusception is a telescoping of a bowel segment into another and it can be a surgical urgency. Most adult intussusceptions arise from a lead point which can be benign or malignant. For this reason, intussusception in adults should undergo surgery. Here we describe a case of ileal inflammatory fibroid polyp (IFP), presenting with ileo-ileal intussusception and obstruction. Case report A 54-year-old Caucasian woman presented for acute abdominal pain. A radiography and a CT of the abdomen were performed, which showed signs of occlusion due to an ileo-ileal intussusception. An urgent laparoscopy was performed, the intussusception was extracorporeally reduced, the ileal segment involved was resected, and an ileo-ileal anastomosis was performed. The intussusception seemed to be caused by a 3-cm intra-mural lesion. Discussion Intussusception is a surgical concern. While most cases are idiopathic in children, 90% of adult intussusceptions are caused by underlying diseases. Therefore, intussusception in adults should undergo surgery. Radiology is necessary for the diagnosis: the CT scan helps localizing the lesion and shows pathognomonic signs. This case report analyzes an intussusception caused by an inflammatory fibroid polyp. Accurate diagnosis of IFP is only possible with histopathological examination, helped by immunohistochemistry. The differential diagnosis is important because some lesions are malignant. Conclusion We reported a case of intussusception caused by an IFP. The diagnosis was made with a CT scan together with intraoperative findings and histopathological examination, which excluded potential differential diagnoses. The patient underwent an explorative laparoscopy, with an ileal resection and anastomosis. Due to the risk of malignancy, surgery is mandatory.